Intraoperative Ex Vivo High-Resolution Sonography: A Novel Technique for the Assessment of Myometrial Invasion in Endometrial Cancer. Issue 9 (1st November 2015) - Basaran, Derman; Salman, Mehmet Coskun; Boyraz, Gokhan; Akata, Deniz; Ozmen, Mustafa; Usubutun, Alp; Ozgul, Nejat; Yuce, Kunter
Abstract : Objective: This study aims to assess the diagnostic performance of a novel intraoperative ex vivo ultrasonography technique in determining deep myometrial invasion (MI) in patients with apparently low-risk endometrial cancer (EC). Methods: This prospective study included patients with type I EC who underwent staging laparotomy at Hacettepe University Hospital from December 2011 to September 2014. After hysterectomy, a radiologist with special training in gynecology examined the uterus ex vivo using a 12-MHz superficial linear probe. The specimen was sent for intraoperative frozen section (FS) analysis. The results were compared with permanent section reports. Results: In total, 45 female patients were eligible for analysis. Intraoperative ex vivo high-resolution sonography (IEVHS) correctly assessed depth of MI in 39 of 45 cases (86.6%) and overestimated it in 5 cases (11.1%). Only 1 case with deep infiltration was underestimated by IEVHS as invasion of less than one half of the myometrium. Frozen section correctly identified depth of MI in 41 of 46 cases (91.1%), overestimated it in 1 case (2.2%), and underestimated it in 3 cases (6.6%). The sensitivity, specificity, positive predictive value, and negative predictive value of IEVHS and FS for assessment of deep MI were 87.5%, 86.4%, 58.3%, and 96.9%, and 62.5%, 97.3%, 83.3%, and 92.3%, respectively. Conclusions: Intraoperative ex vivo high-resolution sonography is a novel technique for assessing MI in EC. Its high sensitivity for deep MI could be useful as an adjunct to FS (enabling pathologists to obtain targeted FS slices) and could improve the accuracy of FS.